First record of the genus Chvalaea Papp & Földvári from Northern Europe (Diptera: Hybotidae) - Kahanpää, Jere (Zootaxa, 2013)
Two species of Chvalaea Papp & Földvári, 2001 are known from Europe. Chvalaea rugosiventris (Strobl, 1910), the type species of the genus, was originally described as a species of Leptopeza Macquart, 1827 (Strobl 1910). It was long known only by the holotype male from Austria, but today it is known also from Croatia and Hungary (Chvála 1983, 2003; Papp & Földvári 2001). Sinclair and Cumming (2000) first recognised Chvalaea as “undescribed genus B”. Papp and Földvári (2001) subsequently described the genus and added a second European species, Chvalaea sopianae Papp & Földvári, 2001, from Hungary. Five additional species of Chvalaea have recently been described by Ale-Rocha (2006) from the Neotropics, including the first description of males of the genus. The genus is also known from China and SE Asia from unpublished records (Adrian Plant, pers. comm.). Ale-Rocha (2007) and Cumming and Sinclair (2009) have published keys for separating Chvalaea from Oropezella based on South American material, but they are also valid for the currently known European species of these genera. Chvalaea sopianae keys out, somewhat uneasily, as an Oropezella in Chvála (1983). It differs from true Oropezella by the heavily sclerotized and rugose abdomen, hooked hind tarsi and the lack of acrostichal and dorsocentral setae on the mesonotum.